Autologous Bone Marrow-Derived Chondrocytes for Patients with Knee Osteoarthritis: A Randomized Controlled Trial - Mir Sadat-Ali; Abdallah S. AlOmran; Sulaiman A. AlMousa; Hasan N. AlSayed; Khalid W. AlTabash; Mohammed Q. Azam; Tarek M. Hegazi; Sadananda Acharya (Advances in Orthopedics)
Background and Objective. The aim of this study was to compare the effect of autologous bone marrow-derived chondrocytes (ABMDCs) with pharmacological management of osteoarthritis of knee (OAK) and assess the benefit of the two in the improvement of pain relief, functional betterment, and quality of life (QOL). Patients and Methods. A prospective, randomized study was undertaken in patients with OAK grades II and III of Kellgren–Lawrence grading (KLG) in two groups. Group I had 5 million of intra-articular ABMDC in the affected joint, and Group II continued the nonsteroidal anti-inflammatory drugs (NSAIDs) and physical therapy as needed. Before the treatment, patients were meticulously examined and data were entered for age, sex, Body Mass Index (BMI), Visual Analogue Scale (VAS), Modified Knee Society Score-Short Form (MKSSSF), and QOL. Patients were followed up for 3, 12, and 24 months to assess efficacy, safety, and tolerability. To assess the cartilage regeneration of the damaged cartilage, magnetic resonance imaging (MRI) was used. Results. There were a total of 60 patients who were followed up. Three patients in Group II were removed from the analysis as they underwent total knee arthroplasty (TKA). A notably significant improvement was noticed in the ABMDC group on all scores of VAS and MKSSSF with P<0.0001. The control group continued to be dissatisfied with the treatment they were taking. Conclusions. This study reveals that a single injection of 5 million of ABMDC was efficient in reducing the symptoms, improving the functional score and betterment of QOL.